Extracts of black and brown rice powders improve hepatic lipid accumulation via the activation of PPARα in obese and diabetic model mice. Issue 11 (2nd November 2017) - Felix, Angelina D R; Takahashi, Nobuyuki; Takahashi, Mami; Katsumata-Tsuboi, Rie; Satoh, Ryo; Soon Hui, Teoh; Miyajima, Katsuhiro; Nakae, Dai; Inoue, Hirofumi; Uehara, Mariko
Abstract: Rice powder extract (RPE) from black and brown rice ( Oryza sativa L. indica ) improves hepatic lipid accumulation in obese and diabetic model mice via peroxisomal fatty acid oxidation. RPE showed PPARα agonistic activity which did not differ between black and brown RPE despite a higher anthocyanin content in black RPE.